2017
DOI: 10.1093/ons/opx232
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation for Essential Tremor: Aligning Thalamic and Posterior Subthalamic Targets in 1 Surgical Trajectory

Abstract: Alignment of VIM and PSA for DBS in ET is feasible and enables intraoperative exploration of both targets in 1 trajectory. This facilitates positioning of electrode contacts in both areas, where multiple effective points of stimulation can be found. In the majority of aligned leads, optimal intraoperative and chronic stimulation were located in the PSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 28 publications
3
40
0
Order By: Relevance
“…Beyond these technical differences, tremor benefit is likely multifactorial where variation in surgical technique, stimulation settings, and outcome variables have all contributed to the mixed findings. For instance, it has been suggested that greater tremor control with DRTC stimulation may also be accompanied by an increased incidence of stimulation‐induced ataxia, a common side effect of VIM DBS that is less frequent with caudal zona incerta stimulation—and perhaps more anterior VIM/ventralis oralis stimulation . Additionally, outcome endpoints within studies may be an additional confound given that most connectivity investigations in ET DBS unfortunately have very short follow‐up intervals.…”
Section: Etmentioning
confidence: 99%
“…Beyond these technical differences, tremor benefit is likely multifactorial where variation in surgical technique, stimulation settings, and outcome variables have all contributed to the mixed findings. For instance, it has been suggested that greater tremor control with DRTC stimulation may also be accompanied by an increased incidence of stimulation‐induced ataxia, a common side effect of VIM DBS that is less frequent with caudal zona incerta stimulation—and perhaps more anterior VIM/ventralis oralis stimulation . Additionally, outcome endpoints within studies may be an additional confound given that most connectivity investigations in ET DBS unfortunately have very short follow‐up intervals.…”
Section: Etmentioning
confidence: 99%
“…Because all discussed tremor targets (Vim, Vo, caudal Zi, Raprl, STN) are located in the same area, many authors have suggested lead trajectories engaging multiple targets through different contacts (Figure 3). on the same trajectory ( Figure 3C), the entry point must be moved laterally [56,57]. This approach has been used successfully in many cases of ET [56,57] and Holmes tremor [58], although no large trial has confirmed its formal utility.…”
Section: Combined Targetsmentioning
confidence: 99%
“…on the same trajectory ( Figure 3C), the entry point must be moved laterally [56,57]. This approach has been used successfully in many cases of ET [56,57] and Holmes tremor [58], although no large trial has confirmed its formal utility. For patients with tremor predominant PD, a posterior trajectory targeting both the DRTT and STN [59] or Vim and STN [60] have also been suggested ( Figure 3D).…”
Section: Combined Targetsmentioning
confidence: 99%
“…In four patients, both the VIM and PSA were targeted. In the other three patients, both regions were not simultaneously targeted because we were unable to align them in one trajectory (Bot et al, 2017).…”
Section: Surgical Proceduresmentioning
confidence: 99%